Electron momentum density of boron-doped carbon nano-onions studied by electron energy-loss spectroscopy. Issue 46 (17th November 2021) - Feng, Zhenbao; Ding, Wei; Lin, Yangming; Guo, Feng; Zhang, Xiaoyan; Song, Tengshuo; Li, Hengshuai; Liu, Cailong
Abstract : Differences between the Compton profile (CP) of pristine carbon nano-onions (CNOs) and the CPs of 1B-CNOs (black), 2B-CNOs (red), and 3B-CNOs (blue). Abstract : Valence Compton profiles (CPs) (electron momentum density projections) of B-doped carbon nano-onions (CNOs) as a function of the boron doping content were obtained by recording electron energy-loss spectra at large scattering angles using a transmission electron microscope, a technique known as electron Compton scattering from solids (ECOSS). The amplitude of the CPs at zero momentum increases with increasing doping content, while the shape of the CPs becomes narrower with increasing doping content. The differences between the profiles of B-doped CNOs and that of pristine CNOs have been clearly observed. These experimental results indicate substantially greater delocalization of the ground-state charge density in B-doped CNOs than in pristine CNOs. The results clearly demonstrate that the ECOSS technique is an efficient and reliable experimental method for studying electron density distributions in solids as a function of the heteroatom doping content.